HANDLING SHARIA ECONOMIC DISPUTES THROUGH NON-LITIGATION AND ITS RELATION TO MASLAḤAḤ - Ardli, Muhammad Nabat; Reza Hilmy Luayyin; Mohammad Arifin (JSE: Jurnal Sharia Economica, 2024)
This research aims to analyze the handling of sharia economic disputes by passing through non-litigation channels with a Maslaḥaḥ asy-Syatibiyy perspective. This research is included in library research using a qualitative descriptive approach. Data collection is obtained through primary and secondary literature review. Data analysis is carried out by normative juridical analysis. then after in-depth analysis, conclusions are drawn. The results of this study indicate that 1) When we try to determining Maslaḥaḥ ash-Syatibiyy said that Maslaḥaḥ should be acceptable to reason and logic, because there is a rational factor. Maslaḥaḥ must be accepted without looking at reasons on the illat, namely on the rules of worship, must not conflict with Shara or qat'i evidence. So that This Maslaḥaḥ must go hand in hand with the purpose of shara, namely maqashid sharia in general,must also go hand in hand with Maslaḥaḥ which is required by shara even though there is no separate evidence, then Maslaḥaḥ which must lift the hardship that emphasizing religion 2) Maslaḥaḥ can be applied or in relevance to the resolution of Islamic economic disputes through non-court channels, namely peace and through the help of mediators because this can provide Maslaḥaḥ because Islam teaches to prioritize peace when there is a dispute between the parties but this is not the case. disputes between the parties but this only applies in the field of This only applies to the field of muamalah or sharia economics again if it relates to worship. 3) The correlation between handling Sharia economic disputes through non-litigation avenues and the concept of Maslaḥaḥ reveals a close relationship between the two. The resolution of Sharia economic disputes through non-litigation methods, such as mediation or negotiation, is often based on fundamental Maslaḥaḥ principles, which emphasize the importance of achieving welfare and justice in Islam